Diabetic state of human coronary artery endothelial cells results in altered effects of bone mesenchymal stem cell‐derived extracellular vesicles - Cynthia M. Xu; Catherine Karbasiafshar; Rayane Brinck‐Teixeira; Mark Broadwin; Frank W. Sellke; M. Ruhul Abid (Physiological Reports, 2023)
Abstract Human bone mesenchymal stem cell‐derived extracellular vesicles (HBMSC‐EV) have been used successfully in animal models of myocardial ischemia, yet have dampened effects in metabolic syndrome through unknown mechanisms. This study demonstrates the basal differences between non‐diabetic human coronary artery endothelial cells (HCAEC) and diabetic HCAEC (DM‐HCAEC), and how these cells respond to the treatment of HBMSC‐EV. HCAEC and DM‐HCAEC were treated with HBMSC‐EV for 6 h. Proteomics, western blot analysis, and tube formation assays were performed. Key metabolic, growth, and stress/starvation cellular responses were significantly altered in DM‐HCAEC in comparison to that of HCAEC at baseline. Proteomics demonstrated increased phosphorus metabolic process and immune pathways and decreased RNA processing and biosynthetic pathways in DM‐HCAEC. Similar to previous in vivo findings, HCAEC responded to the HBMSC‐EV with regenerative and anti‐inflammatory effects through the upregulation of multiple RNA pathways and downregulation of immune cell activation pathways. In contrast, DM‐HCAEC had a significantly diminished response to HBMSC‐EV, likely due to the baseline abnormalities in DM‐HCAEC. To achieve the full benefits of HBMSC‐EV and for a successful transition of this potential therapeutic agent to clinical studies, the abnormalities found in DM‐HCAEC will need to be further studied.